2022
DOI: 10.1177/17474930221115892
|View full text |Cite
|
Sign up to set email alerts
|

Posterior circulation stroke from diagnosis to management, including recent data on thrombectomy for basilar artery occlusion from the BAOCHE and ATTENTION trials

Abstract: Posterior circulation stroke accounts for one-fifth of all strokes, but despite this, it has been a neglected area. It can present considerable challenges in diagnosis, and there are fewer studies examining optimal treatment compared with anterior circulation stroke. This month's issue of IJS attempts to address this balance. We have a particular focus on posterior circulation stroke with coverage of areas ranging from diagnosis, through acute treatment and thrombectomy, to secondary prevention. This initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For basilar artery occlusion, recent positive randomized trials and looming regulatory decisions provocatively ask whether any type of advanced neurovascular imaging is necessary. 7 The collateral routes, associated perfusion maps, lesion size, association with underlying etiology of occlusion, and timecourse of lesion evolution may not be relevant or critical in medical decision-making for evaluation and treatment of basilar artery occlusion.…”
Section: Clinical Paradigms—large Core Ischemia Distal Occlusions And...mentioning
confidence: 99%
“…For basilar artery occlusion, recent positive randomized trials and looming regulatory decisions provocatively ask whether any type of advanced neurovascular imaging is necessary. 7 The collateral routes, associated perfusion maps, lesion size, association with underlying etiology of occlusion, and timecourse of lesion evolution may not be relevant or critical in medical decision-making for evaluation and treatment of basilar artery occlusion.…”
Section: Clinical Paradigms—large Core Ischemia Distal Occlusions And...mentioning
confidence: 99%
“…Although there is limited data available on the efficacy and safety of MT in the posterior vasculature, recent studies have demonstrated the effectiveness of this procedure compared to the best non-invasive treatment 2 , 3 . Acute ischemic strokes in the posterior cerebral vessels are estimated to account for 13.5–20% of all strokes 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Although a preponderance of evidence had previously demonstrated equipoise between endovascular thrombectomy (EVT) and medical therapy alone for the treatment of acute BAO, recent randomized clinical trial data have, for the first time, demonstrated a clinical benefit to EVT in the posterior circulation. 4 This study [termed the BAO National Inpatient Sample (BArONIS) study] draws on real-world populationlevel data from the United States to examine the association between EVT and clinical outcomes in acute BAO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Basilar artery occlusions (BAO), which account for approximately 10% of large vessel strokes, 2 confer especially poor outcomes, as severe deficits persist in 80% or more of patients following treatment and as many as 40% may progress to mortality 3 . Although a preponderance of evidence had previously demonstrated equipoise between endovascular thrombectomy (EVT) and medical therapy alone for the treatment of acute BAO, recent randomized clinical trial data have, for the first time, demonstrated a clinical benefit to EVT in the posterior circulation 4 . This study [termed the BAO National Inpatient Sample (BArONIS) study] draws on real‐world population‐level data from the United States to examine the association between EVT and clinical outcomes in acute BAO patients.…”
Section: Introductionmentioning
confidence: 99%